Influence of dietary components on the risk of urinary tract stones - Miśkiewicz, Marek; Głodzik, Michał; Stencel, Katarzyna; Stelmaszak, Karina; Wojtasik, Monika; Ogiegło-Kowalczyk, Aleksandra; Samborska, Julia; Więckowiak, Paweł; Łęcka, Martyna; Żak, Katarzyna (Journal of Education, Health and Sport, 2023)
Urinary tract stones are a common condition that significantly reduces quality of life. A proper diet is an important factor in the prevention and treatment of lithiasis and, for this reason, dietary interventions have become an essential part of treatment. In our review of the literature, we analysed the individual components of diet in terms of the risk of developing urinary tract stones. A number of dietary guidelines have been developed to reduce lithogenic factors in the urine, such as calcium oxalate, calcium phosphate and uric acid. Current guidelines recommend increasing the intake of fluids, increasing the intake of fruit and vegetables, using a balanced calcium supplementation and limiting the supply of sodium and especially animal protein. Based on these recommendations, a vegetarian diet containing dairy products combined with calcium supplementation appears to have the lowest risk of developing urinary stones. However, there are still many uncertainties in this area, and research needs to continue and be expanded to include the influence of diet type on the risk of lithiasis. This will allow us to gain a better understanding of the factors influencing the disease process and to create clear guidelines in the field of urolithiasis in the future.